Decision-Making in Light of Teaching Code of Ethics: Perceptions of Omani School Educators - Wajeha Al-Ani (Sultan Qaboos University, 2018)
This study aimed to identify the perspective of Omani educators on the status of decision making in light of the teaching profession's code of ethics. The study used a qualitative research design where semi-structured interviews were conducted with 49 school educators. NVivo was used for data analysis. Results of the study showed that educators view the ethics of the teaching profession as a collection of good dispositions and values such as sincerity, care, and professional consciousness. Lack of respect and decreasing commitment levels are the most common problems among students. The interviewees used mostly guidance and advice, followed by trying to understand the problem, and referring cases to the school social counselor. Referring to the school bylaws on how to solve problems received the lowest percentage. The results also showed that the school's social counselor plays a big role and he/she is often consulted when trying to understand problems or solving behavioral problems. Other entities that are referred to are the school administration, school colleagues and the educational supervisor. The study also showed that educators use various sources as a framework for their decisions concerning students' behavior problems, such as religion, social norms and values, personal values and dispositions, school policies, and personal experience.